Electrospray-deposition of graphene electrodes: a simple technique to build high-performance supercapacitors1. Issue 20 (28th May 2015) - Tang, Huaichao; Yang, Cheng; Lin, Ziyin; Yang, Quanhong; Kang, Feiyu; Wong, Ching Ping
<x xml:space="preserve">Abstract</x> Three-dimensional porous graphene electrodes prepared by electrostatic spray deposition can be used in high performance supercapacitors.